2022
DOI: 10.1186/s13293-022-00441-3
|View full text |Cite|
|
Sign up to set email alerts
|

Consideration of sex and gender differences in addiction medication response

Abstract: Substance use continues to contribute to significant morbidity and mortality in the United States, for both women and men, more so than any other preventable health condition. To reduce the public health burden attributable to substances, the National Institute on Drug Abuse and the National Institute on Alcohol Abuse and Alcoholism have identified that medication development for substance use disorder is a high priority research area. Furthermore, both Institutes have stated that research on sex and gender di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 211 publications
0
24
0
Order By: Relevance
“…Given the rates of alcohol-related mortality, it is important to acknowledge the limited knowledge of how current pharmacologic treatments for AUD specifically affect women. As emphasized by McKee and McRae-Clark, the development of medications for AUD has often overlooked potential sex and gender differences. The US Food and Drug Administration–approved medications for AUD, such as disulfiram, naltrexone, and acamprosate, have been studied primarily in men, leaving a knowledge gap regarding their association with mortality outcomes in women .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the rates of alcohol-related mortality, it is important to acknowledge the limited knowledge of how current pharmacologic treatments for AUD specifically affect women. As emphasized by McKee and McRae-Clark, the development of medications for AUD has often overlooked potential sex and gender differences. The US Food and Drug Administration–approved medications for AUD, such as disulfiram, naltrexone, and acamprosate, have been studied primarily in men, leaving a knowledge gap regarding their association with mortality outcomes in women .…”
Section: Discussionmentioning
confidence: 99%
“…As emphasized by McKee and McRae-Clark, the development of medications for AUD has often overlooked potential sex and gender differences. The US Food and Drug Administration–approved medications for AUD, such as disulfiram, naltrexone, and acamprosate, have been studied primarily in men, leaving a knowledge gap regarding their association with mortality outcomes in women . Although these medications have shown potential in improving health outcomes, their effectiveness in reducing alcohol-related mortality remains uncertain, particularly for women .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported a typo in the first sentence of the "Abstract" and the "Introduction". The first sentences of both should read as follows: “Substance use continues to contribute to significant morbidity and mortality in the United States, for both women and men, more so than any other preventable health condition.” …”
Section: Correction To: Biology Of Sex Diferences (2022) 13:34 101186...mentioning
confidence: 99%
“…Alcohol use disorder (AUD) is a devastating neuropsychiatric illness, characterized by a high propensity to relapse even after extended abstinence. It has become increasingly evident that existing pharmacotherapies are not equally effective in men and women [ 1 3 ]. Among individuals that engage in heavy drinking, women exhibit greater alcohol craving in response to stress than men [ 4 ] which places them at elevated risk of stress-induced relapse.…”
Section: Introductionmentioning
confidence: 99%